The effect of combined salinities and elevated temperature on protein, energy requirements for maintenance and feed utilization of red tilapia (Oreochromis sp.) : - Tran, Thi Thap Hieu (Can Tho university, 2018)
This book introduce about effect of salinity and elevated temperature on maintenance requirements and efficiency of feed utilization. The effect of salinity at elevated temperature on protein and lipid requirements in red tilapia.